Hubungan antara Faktor Sokongan Pendidikan dan Minat Pelajar dalam Bidang Keusahawanan - Amran , Nurzulaikha; Abu Seman, Noor Aslinda (Research in Management of Technology and Business, 2021)
Entrepreneurial activities move the country’s economy and ensure the well -being of society. In the national education system, entrepreneurship education has been introduced for more than 30 years at the level of educational institutions. Yet, issues related to the lack of students influenced by interest in entrepreneurship are still a topic of discussion. Educational support factors are very important in influencing students’ interest in entrepreneurship. This study aims to identify the level of educational support factors and also examine how the educational support factors that are co -curriculum and curriculum and pedagogy in influencing students’ interest in entrepreneurship. Based on Krejie and Morgan’s sample size table, a total of 302 respondents were involved in this study. However, the total return of the questionnaire was only 164 sets of questions. This study used simple sampling by distributing questionnaires. The analysis of this study used descriptive and correlation methods. The data collected were analyzed using Statistical Package for Social Science (SPSS) software. The study found that there is a positive relationship between educational support factors and students’ interest in entrepreneurship. This study can be a guide to the university or lecturers in planning the best strategy to apply the interests of students in the field of entrepreneurship.